Deep-time origin of tympanic hearing in crown reptiles - Bronzati, Mario; Vieceli, Felipe M.; Botezelli, Vitoria S.; Godoy, Pedro L.; Montefeltro, Felipe C. [UNESP]; Nassif, Jann P.M.; Luzete, Juliana; Ribeiro, Douglas [UNESP]; Yan, C.Y. Irene; Werneburg, Ingmar; Kohlsdorf, Tiana (Elsevier, 2024)
The invasion of terrestrial ecosystems by tetrapods (c. 375 million years [Ma]) represents one of the major evolutionary transitions in the history of life on Earth. The success of tetrapods on land is linked to evolutionary novelties. Among these, the evolution of a tympanic ear contributed to mitigating the problem of an impedance mismatch between the air and the fluid embedding sound-detecting hair cells in the inner ear.1,2,3 Pioneering studies advocated that similarities in the tympanic ear of tetrapods could only result from a single origin of this structure in the group,4,5 an idea later challenged by paleontological and developmental data.4,6,7,8 Current evidence suggests that this sensory structure evolved independently in amphibians, mammals, and reptiles,1,6 but it remains uncertain how many times tympanic hearing originated in crown reptiles.9,10 We combine developmental information with paleontological data to evaluate the evolution of the tympanic ear in reptiles from two complementary perspectives. Phylogenetically informed ancestral reconstruction analyses of a taxonomically broad sample of early reptiles point to the presence of a tympanic membrane as the ancestral condition of the crown group. Consistently, comparative analyses using embryos of lizards and crocodylians reveal similarities, including the formation of the tympanic membrane within the second pharyngeal arch, which has been previously reported for birds. Therefore, both our developmental and paleontological data suggest a single origin for the tympanic middle ear in the group, challenging the current paradigm of multiple acquisitions of tympanic hearing in living reptiles.
Keywords: embryos; evo-devo; evolution; fossils; integrative biology; paleontology; reptiles; tympanic hearing; tympanic membrane